STAKEHOLDER PERCEPTIONS OF AI USE IN EDUCATION: Perspectives of Teachers, Students, and Parents in Indonesia - Akbar, Gugun Geusan; Kania, Ikeu; Uhmudin, Aceng; Fadlurohman, Mochammad Iqbal; Nurliawati, Nita (jfpublisher, 2025)
The research examines how stakeholders in Garut Indonesia view Artificial Intelligence (AI) applications for inclusive education while filling the knowledge deficit about AI's contribution to fair learning environments. The research investigates how AI benefits, challenges, and ethical issues affect inclusive education from teacher and student and parental viewpoints. The research used a mixed-methods design to gather data through in-depth interviews and focus group discussions and surveys with 120 participants distributed among 40 teachers and 50 students and 30 parents for three months. The research shows AI provides three main advantages to inclusive education: personalized learning (students’ mean rating: 4.5), adaptability, and resource accessibility. The study identifies three major obstacles which include data privacy concerns (parents’ mean rating: 4.3) and technology dependency and reduced teacher-student communication. The educational staff views AI technology as an educational resource yet they prioritize the preservation of human relationships between teachers and students while parents focus on data protection and developmental threats. The study faces limitations because it focuses on Garut and has a short research duration which restricts the ability to generalize findings. The recommendations call for strong data protection measures and teacher training and parental education to solve ethical problems such as algorithmic bias. The research demonstrates how AI should coexist with human interaction to achieve educational equity while proposing future investigations into cognitive-socio-emotional effects and adaptive policy development.